Pengaruh Pemahaman dan Tingkat Kepercayaan Masyarakat terhadap Rendahnya Inklusi Keuangan Berbasis Fintech di Kabupaten Asahan - Siregar, Tetty Handayani; Dewi, Nurul Aulia; Muda, Iskandar; Soemitra, Andri; Yusrizal (JSE: Jurnal Sharia Economica, 2025)
This study aims to analyze the influence of public understanding and trust levels on low fintech-based financial inclusion in Asahan Regency. The phenomenon of inequality between high digital penetration and low fintech adoption in rural areas is the main research background. The approach used is quantitative with a survey method of 100 respondents spread across 25 sub-districts, using a Likert scale-based questionnaire instrument. Data were analyzed using SmartPLS 4.0 software with the Structural Equation Modeling Partial Least Square (SEM-PLS) approach. The results of the study indicate that public understanding and trust have a significant influence on digital financial inclusion. This is proven through hypothesis testing with t-statistic values ​​above 1.96 and p-value <0.05, respectively. The R-Square value of 0.488 indicates that the two independent variables explain almost all of the variation in financial inclusion. These findings strengthen the Technology Acceptance Model theory and consumer trust theory, and emphasize the importance of literacy strategies and consumer protection in supporting financial inclusion. This study also develops a micro index of fintech inclusion based on the dimensions of access, use, and service quality. These findings are expected to be the basis of policies for local governments, regulators, and industry players in expanding inclusive finance in remote areas more effectively